Penerapan model discovery learning berbatuan edpuzzle untuk meningkatkan kemampuan pemahaman matematis siswa SMP kelas VII di SMPN 3 Cikalongwetan - Gunawan, Guntur; Yuliani, Anik; Amelia, Risma (IKIP Siliwangi, 2024)
The purpose of this study is to examine the application of the discovery learning model assisted by edpuzzle on the mathematical understanding ability of class VII students in terms of achievement, improvement, and completeness of learning objectives. The method used is a quasi-experimental method with two classes as samples, namely the experimental class and the control class. The technique used to collect data is the mathematical understanding ability question instrument. Data processing is analyzed using the Microsoft Excel application and SPSS 22 software. The results of the study explain that the achievement, improvement and completeness of the achievement of learning objectives for mathematical understanding abilities of class VII junior high school students with the discovery learning model assisted by edpuzzle are better than those using conventional learning.